Bowel Cleansing Protocol in Colonoscopy: Does It Affect Blood Thiamine Level? - Rabbinu Rangga Pribadi; Virly Nanda Muzellina; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2020)
Background: The burden of vitamin B1 or thiamine deficiency in patients undergoing digestive surgery is quite enormous. In the field of gastroenterology, pre-colonoscopy preparation might affect thiamine level. However the burden is not well defined. This study was conducted to confirm whether there is significant decrease of blood thiamine level in post-colonoscopy compared to pre-colonoscopy group.Method: This cross-sectional study was carried out at gastrointestinal endoscopy center of Cipto Mangunkusumo National General Hospital, Jakarta from October 2018 to January 2019. The inclusion criteria were patients equal or more than 18-year-old who underwent colonoscopy. The exclusion criteria were malnutrition, history of post-gastrointestinal resection, definitive diagnosis of cancer, and chronic alcoholism.Results: The median value of blood thiamine level is 58 (20-78) for pre-colonoscopy group and 58 (25-79) for post colonoscopy group (p=0.31).Conclusion: There was no significant decrease of blood vitamin B1 level in post-colonoscopy compared to pre-colonoscopy group.